Improvement in the secretory expression of recombinant Candida rugosa lipase in Pichia pastoris. Issue 12 (December 2015) - Kuo, Ting-Chun; Shaw, Jei-Fu; Lee, Guan-Chiun
Graphical abstract: Highlights: Two combined processes were developed to improve Lip2 secretion in P. pastoris . The process includes gene copy amplification and low-temperature culture. The process results in a maximal 32-fold increase in Lip2 secretion. The steady-state LIP2 mRNA amount determines the maximal secretion level of Lip2. Abstract: The yeast Candida rugosa can secrete a mixture of lipase isoenzymes (Lips), which have been widely applied in industry. Eight Lip genes ( LIP1 to LIP8 ) have been identified and are expressed in Pichia pastoris . However, the expression level was not sufficient for economical industrial application. In this study, two combined processes of antibiotic selection and low-temperature culture efficiently elicited a high-level secretion of recombinant Lip2 in P. pastoris . The LIP2 gene copy number of the Pichia transformants was increased by sequential selections at gradually increasing Zeocin concentrations. After the first selection at 500 μg/mL of Zeocin, three clones (500-clones) with 2.4-fold to 5.8-fold improvement in Lip2 secretion were identified from 105 survival clones through lipase activity screening. Although the maximum number of LIP2 gene copy was four among these three 500-clones, the lipase secretion of the four-copy clone was not higher than that of the three-copy clone. The effects of multiple gene copy number and low culture temperature resulted in a maximal 32-fold increase in Lip2 secretion. This method could be applied to other Lip isoforms to enhance their yields in P. pastoris .